2022
DOI: 10.1101/2022.11.22.22282629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Expansion of SARS-CoV-2 Variants of Concern: Dispersal Patterns and Influence of Air Travel

Abstract: In many regions of the world, the Alpha, Beta and Gamma SARS-CoV-2 Variants of Concern (VOCs) co-circulated during 2020-21 and fueled waves of infections. During 2021, these variants were almost completely displaced by the Delta variant, causing a third wave of infections worldwide. This phenomenon of global viral lineage displacement was observed again in late 2021, when the Omicron variant disseminated globally. In this study, we use phylogenetic and phylogeographic methods to reconstruct the dispersal patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…These results are consistent with previous investigations of VOCs in England and other countries ( 27, 35 ), highlighting the ineffectiveness of international travel restrictions when applied after the detection of local transmission, when they are applied to too few countries, and not in combination with local control measures. This is especially true when countries outside the presumed origin location have rapidly growing epidemics and become major exporters of the VOC, as highlighted by the epidemic of BA.1 in NYC and continued exponential growth of importations into England in early December 2021 ( 36 ). More generally, the practical value of targeted travel restrictions is further limited by the fact that there are often multiple pathways connecting any two countries in the global transportation network ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous investigations of VOCs in England and other countries ( 27, 35 ), highlighting the ineffectiveness of international travel restrictions when applied after the detection of local transmission, when they are applied to too few countries, and not in combination with local control measures. This is especially true when countries outside the presumed origin location have rapidly growing epidemics and become major exporters of the VOC, as highlighted by the epidemic of BA.1 in NYC and continued exponential growth of importations into England in early December 2021 ( 36 ). More generally, the practical value of targeted travel restrictions is further limited by the fact that there are often multiple pathways connecting any two countries in the global transportation network ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, following an importation, viral lineages spread in the country widely and circulated more intensely in key regions in north and central Chile. While continuous phylogeographic analyses are prone to sampling biases (60, 61), the distribution and circulation of these lineages around important urban areas and locations attractive for tourists suggests that viral movements in the country follow from human movements, as has been reported previously (1, 4, 9, 30, 31, 62, 63). The invasion process appears to be explained by the connectivity between comuna pairs, making human movement estimates from mobile phone usage an important predictor of arrival times of a new viral lineage into different comunas.…”
Section: Discussionmentioning
confidence: 64%
“…Because phylogenetic inferences are influenced by sampling biases and model specification we use independent datasets to correlate estimates made from genomic data. Previous studies have shown that the number of international travellers coming into a territory can be used to help infer the expected number of SARS-CoV-2 case introductions (30, 31). We calculated an estimated importation intensity index (EII) based on the estimated cases for each variant in a potential source country and the total movements from that country into Chile.…”
Section: Main Textmentioning
confidence: 99%
“…9 Two new lineages, BA.4 and BA.5 have contributed to the fifth wave of infections in South Africa and have spread to many countries. 7,10 The spike proteins of BA.4 and BA.5 were identical to BA.2, except for the addition of 69-70del, L452R, and F486V. In addition to the spike protein mutation, BA.4 has a triple amino acid deletion in NSP1:141-143del which is located in the nonstructural protein 1 (NSP1) region of the SARS-Cov-2 genome, whilst BA.5 has the D3N mutation in the membrane protein region (M:D3N).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the spike protein mutation, BA.4 has a triple amino acid deletion in NSP1:141-143del which is located in the nonstructural protein 1 (NSP1) region of the SARS-Cov-2 genome, whilst BA.5 has the D3N mutation in the membrane protein region (M:D3N). 10,11 An urgent need for variant phenotyping of circulating sublineage is necessary for epidemiological surveillance during Omicron surges. Genomic and real-time surveillance played a pivotal role in sustaining this state of elimination and also realized which new variants might gain a foothold and trigger new waves of infection.…”
Section: Introductionmentioning
confidence: 99%